2007
DOI: 10.1097/01.tp.0000269615.91036.52
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antithymocyte Globulin on Anti–Human Leukocyte Antigen Antibody Detection Assays

Abstract: We conclude that ATG produces positive results in anti-HLA antibody testing, and treatment to remove ATG abolishes this effect. This treatment allows ATG-treated patients to be monitored for anti-HLA antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…However, the current study failed to demonstrate any in vivo impact of IVIG or rATG on antibody-secreting PCs in sensitized renal allograft patients. Pretransplant treatment with rATG using two different dosing regimens to achieve therapeutic levels in the serum (25) did not alter the total number of bone marrow-derived ASCs or antibody production. The findings that desensitization protocols involving multiple pretransplant PP/IVIG alone or in combination with pretransplant rATG have no impact on ASCs number and function in vivo agree with our previous histologic studies of splenic B cells (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the current study failed to demonstrate any in vivo impact of IVIG or rATG on antibody-secreting PCs in sensitized renal allograft patients. Pretransplant treatment with rATG using two different dosing regimens to achieve therapeutic levels in the serum (25) did not alter the total number of bone marrow-derived ASCs or antibody production. The findings that desensitization protocols involving multiple pretransplant PP/IVIG alone or in combination with pretransplant rATG have no impact on ASCs number and function in vivo agree with our previous histologic studies of splenic B cells (17).…”
Section: Discussionmentioning
confidence: 99%
“…The viability of CD138 + cells was >80% at 72 h. Initial attempts using conventional ELISpot matrices of nitrocellulose or polyvinylidene fluoride were unsuccessful. In addition, Table 1: Demographics of patients in each study group including: Group 1: control group (nonsensitized subjects, n = 4); Group 2: sensitized subjects at baseline (prior to any therapy, n = 9); Group 3: sensitized subjects treated with multiple pretransplant plasmaphereses (PP) and low dose IVIG (n = 4); Group 4: sensitized subjects treated with PP/IVIG plus multiple doses of pretransplant rATG (all of these patients were studied at baseline and after rATG treatment and thus all were included in Group 2, n = 4) and; Group 5: sensitized subjects who were treated with a single high dose of rATG (5 mg/kg IV) and then received daily PP/IVIG (n = 7, of note, two of these patients were studied at baseline and thus were also included in group 2) The rATG has been shown to interfere with both flow crossmatch and SAFB assays and was removed from serum samples using sheep anti-rabbit IgGcoated synthetic beads (Dynabeads M-280, Invitrogen) as previously described (24,25).…”
Section: Asc Alloantibody Specificity Assaymentioning
confidence: 99%
“…Interestingly, Gloor et al [25] from Mayo Clinic showed that in vivo treated sera from ATG-treated patients produced positive test results for T-cell complement-dependent cytotoxicity and T- and B-cell flow cytometric (FXM), while the B-cell complement-dependent cytotoxicity cross-match remained negative. Solid-phase assays HLA class I and II assays based on antigen-coated microspheres and enzyme-linked immunosorbent assay (ELISA) were minimally affected using in vivo treated sera.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…When pretransplant plasmapheresis (PP) was performed, the serum DSA determined was from serum collected prior to PP treatment. When thymoglobulin was used, it was extracted from the serum prior to assaying (4 (6). (2).…”
Section: Donor-specific Alloantibody (Dsa) Is An Increasingly Common mentioning
confidence: 99%